1974
DOI: 10.1111/j.1365-3180.1974.tb01075.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nutrient status on paraquat activity

Abstract: Experiments with young plants of seven cultivars and species in the Gramineae (Lolium perenne L. cv. S 23, Lolitim multiflorum Lam. cv. S 22, Lolntm muUifiorum Lam. cv. Tetrone, Triticum aestivum L. cv. Janus, Avena sativa L. cv. Peniarth, Hordeum vulgare L. cv. Zephyr, Avena fatua L.), showed that those grown at a high nitrogen level were more susceptible lo paraquat than those grown at a low level. Similarly, high levels of phosphorus increased the susceptibility of plant5 of A. saliva to this herbicide. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The results presented here agree with Lutman et al. (1974) and provide a closer insight into the relationship between nitrogen response and herbicide dose–response of weeds.…”
Section: Discussionsupporting
confidence: 86%
“…The results presented here agree with Lutman et al. (1974) and provide a closer insight into the relationship between nitrogen response and herbicide dose–response of weeds.…”
Section: Discussionsupporting
confidence: 86%
“…These experiments have shown that when the amount of paraquat available to the leaf was similar over the three nitrogen levels, then the low nitrogen leaves were more susceptible than the high nitrogen ones. Therefore the greater tolerance of the low nitrogen plants sprayed with paraquat found in the earlier whole plant experiments (Lutman et al, 1974) was not due to a greater 'intrinsic' tolerance of the leaves.…”
Section: Discussionmentioning
confidence: 64%
“…In previous experimenls it was shown that the suscepiibilily to paraquat of young cereals and grasses was influenced by their nitrogen status (Lutman et al, 1974). When sprayed with paraquat, plants grown in soils of high nitrogen status were more susceptible than those grown in soils of lower nitrogen status.…”
Section: Introductionmentioning
confidence: 93%
“…Data from previous experiments showed that plants grown at a high nitrogen status were more susceptible to paraquat than plants grown at a low nitrogen status (Lutman et al, 1974). The results of the experiments described in this paper support the hypothesis that the greater susceptibility of the high nitrogen plants was because they intercepted and retained more paraquat than the low nitrogen plants.…”
Section: Wcttabilitymentioning
confidence: 99%
“…Experiments described in a previous paper (Lutman, Sagar, Marshall & Headford, 1974) indicated that young cereal plants grown under high nitrogen conditions were more susceptible to paraquat than those grown under low nitrogen conditions. In this paper further experiments are described which attempt to explain these results.…”
Section: Introductionmentioning
confidence: 99%